Tackling carbapenem resistance: ceftazidime - avibactam in contemporary clinical scenarios - Maladkar, Manish; Patil, Shrikant; Anchan, Namita (International Journal of Advances in Medicine, 2024)
Antimicrobial resistance poses a formidable challenge in treating severe infections, with the prevalence of extended-spectrum beta-lactamase (ESBL) - producing, Klebsiella pneumoniae carbapenemase (KPC) - producing, and multidrug-resistant (MDR) organisms on the rise. This necessitates careful consideration of various factors, including local resistance patterns, patient-specific characteristics, and drug properties, in treatment decisions for critically ill patients. Ceftazidime-Avibactam demonstrates efficacy against aerobic Gram-negative bacteria and offers a crucial advancement against carbapenem-resistant organisms (CRO) with its effectiveness against key pathogens, including ESBL, AmpC, KPC, and OXA-48-producing Enterobacteriaceae and drug-resistant P. aeruginosa. Ceftazidime-Avibactam emerges as a valuable option for critically ill patients with limited treatment choices. The drug’s excellent safety profile demonstrated in clinical trials, further positions it as a crucial addition to antimicrobial treatment options. As the global threat of drug-resistant bacteria grows, Ceftazidime-Avibactam plays a pivotal role in addressing this challenge and offers a promising solution for critically ill patients facing infections caused by antimicrobial-resistant pathogens. The article delves into therapeutic efficacy and the prospective role of Ceftazidime-Avibactam in managing MDR Gram-negative organisms, underscoring the critical role of appropriate antibiotic administration in reducing mortality associated with Gram-negative infections.